The impact of the COVID-19 event on the financial stability of US banks - Dr. David warner,; Dr. Michal sticks, (Al-Qanṭara, 2022)
The use of changes in investors' forward-looking net long hedging choices — an indicator of investors' risk-based growth expectations — to determine the effect of a change in the Federal Reserve's capital buffer requirement on banks' financial soundness is the study's primary innovation. I show that net hedging factor data reveals significant causal relationships between financial soundness indicators and the Federal Reserve's capital buffer requirement. My findings also show that lowering the capital buffer requirement for banking systems improves both regulatory capital and Tier-1 capital. Keywords- financial stability of US banks